Use of innovative methods in teaching subjects (Journal of Pedagogical Inventions and Practices, 2022)
Simple lectures, which are the teacher's hourly monologues, are no longer interesting to modern students. They are easily bored and express it openly. A university or vocational school teacher must now not only engage but also captivate the audience's attention. For these goals, cutting-edge instructional technologies are being developed.